“Neither knowing nor not knowing”: Existential Anxiety and Ecological Certainty in the Poetry of W.S. Merwin - Peter Vernon (Transatlantica)
This paper argues that Merwin’s poetry is constantly aware of the dangers caused by mankind’s impact on the environment, which has the effect of separating humanity from the natural world. In this situation Merwin is certain of the rights of animals and oppressed peoples, yet his poetic voice is less certain of his position in the world. His poetry is suffused with a sense of absence, with the loss of friends, homes, animals, and family. These losses and consequent grief are examined in The Vixen, The Folding Cliffs, and other volumes collected in Migration: New and Selected Poems. Merwin’s poetry expresses loss through apophatic arguments, and rhetorically through praeteritio, and antithesis, which create an elegiac tone in the evocation of place. Since he sees the world holistically, he has frequent recourse to synesthesia. Merwin writes of loss and argues from the negative, but paradoxically although all has been lost, nevertheless something beautiful, sensual, and permanent remains—the poems themselves: Merwin’s lost world held in words.